Double Diapering Ineffectiveness in Avoiding Adduction and Extension in Newborns Hips - Maurizio De Pellegrin; Chiara Maria Damia; Lorenzo Marcucci; Desiree Moharamzadeh (MDPI AG, 2021)
Hip flexion and abduction is fundamental for developmental dysplasia of the hip (DDH) treatment. At present, double diaper treatment has been inappropriately adopted when DDH is suspected. The aim of this study was to verify whether double diapers influence a newborn's hip position. Here, we studied 50 children (23 female; 27 male; average age 62.33 ± 20.50 days; average birth weight 3230 ± 447 g) with type I hips according to Graf. At the same time of the ultrasound (US) examination, the following hip positions were measured using a manual protractor: (1) spontaneous position, supine on the outpatient bed without a diaper; (2) spontaneous position, with a double diaper; and (3) squatting position on the caretakers' side. Statistical analysis was performed with a t-test to compare between (1) the spontaneous position without a diaper and with double diapers; (2) the spontaneous position with double diapers as well as the squatting position on the caretakers' side with a diaper. The comparison between the hip position without diaper and with double diapers was statistically not significant for all measurements, i.e., right hip flexion (p < 0.33), left hip flexion (p < 0.34), and right and left hip abduction (p < 0.87). The comparison between the hip position with double diapers and on the caretakers' side was statistically significant for all measurements, i.e., right hip flexion (p < 0.001), left hip flexion (p < 0.001) and right and left hip abduction (p < 0.001). We found that the use of double diapers did not affect hip position, while the position formed on the caretaker's side shows favorable influence.